2020
DOI: 10.1002/jgf2.358
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis with skin lesions localized to the scalp: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Our one of the most interesting findings that the psoriatic involvement of the scalp and body folds enhanced the risk of fractures and falls is similarly as challenging to answer as why a number of features, such as scalp lesions, nail dystrophy, and flexural lesions (of these scalp laesions most significantly) increase the risk of PsA in patients with psoriasis 8 . Some authors have shown, that severe arthritis in the fingers and extremities can be observed in patients with scalp psoriasis 22 but there are no similar observations in patients with flexural psoriasis. In search for possible underlying mechanisms, Stanmore and al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our one of the most interesting findings that the psoriatic involvement of the scalp and body folds enhanced the risk of fractures and falls is similarly as challenging to answer as why a number of features, such as scalp lesions, nail dystrophy, and flexural lesions (of these scalp laesions most significantly) increase the risk of PsA in patients with psoriasis 8 . Some authors have shown, that severe arthritis in the fingers and extremities can be observed in patients with scalp psoriasis 22 but there are no similar observations in patients with flexural psoriasis. In search for possible underlying mechanisms, Stanmore and al.…”
Section: Discussionmentioning
confidence: 99%
“…8 Some authors have shown, that severe arthritis in the fingers and extremities can be observed in patients with scalp psoriasis22 but there are no similar observations in patients with flexural psoriasis. In search for possible underlying mechanisms, Stanmore and al.…”
mentioning
confidence: 99%